2009
DOI: 10.1186/1475-2875-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Failure of artesunate-mefloquine combination therapy for uncomplicated Plasmodium falciparum malaria in southern Cambodia

Abstract: Background: Resistance to anti-malarial drugs hampers control efforts and increases the risk of morbidity and mortality from malaria. The efficacy of standard therapies for uncomplicated Plasmodium falciparum and Plasmodium vivax malaria was assessed in Chumkiri, Kampot Province, Cambodia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
188
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(198 citation statements)
references
References 21 publications
6
188
1
3
Order By: Relevance
“…The multiplication extent at the baseline of 13% was a clear cause of concern as reported earlier, 41 because pfmdr1 multicopy occurrence seems to be associated with longer parasite clearance time and higher initial parasitaemias. 42 Luckily, no significant difference in multiplication extent could be detected in a 5-year time span. A telltale for the increased copy number in the isolates from Suriname could be the absence of the pfmdr1 N86Y mutation, which has been reported as a negative marker for increased copy number.…”
Section: Discussionmentioning
confidence: 93%
“…The multiplication extent at the baseline of 13% was a clear cause of concern as reported earlier, 41 because pfmdr1 multicopy occurrence seems to be associated with longer parasite clearance time and higher initial parasitaemias. 42 Luckily, no significant difference in multiplication extent could be detected in a 5-year time span. A telltale for the increased copy number in the isolates from Suriname could be the absence of the pfmdr1 N86Y mutation, which has been reported as a negative marker for increased copy number.…”
Section: Discussionmentioning
confidence: 93%
“…Earlier studies showed that mefloquine was effective against P. falciparum in vitro, and showed low IC 50 values of 28.7-130 nM. 27,34,35 Mefloquine showed high IC 50 values (272 μM) for mammalian cells (dog neurons). 36 Doses of pepstatin A and mefloquine for bovine babesiosis most effectively suppressed parasite growth compared with other drugs that have been tested for the treatment of babesiosis.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo growth inhibition assay for pepstatin A, mefloquine, and pepstatin A/ mefloquine combinations (2.5 mg/kg/2.5 mg/kg and 5 mg/kg/ 5 mg/kg) was performed in BALB/c mice as described. 8,34 Twenty-eight week-old female BALB/c mice were divided into five groups of four mice and intraperitoneally inoculated with 1 + 10 6 B. microti-infected erythrocytes. In the first group, mefloquine dissolved in DMSO was administered at a dose rate of 5 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Cambodian samples were collected between August 2006 and December 2007 as part of a chloroquine treatment trial at the Chumkiri health center in Kampot Province. 27 Details of the study have previously been published. Antirelapse therapy with primaquine was not given.…”
Section: Methodsmentioning
confidence: 99%